Changing the selectivity profile – from substrate analog inhibitors of thrombin and factor Xa to potent matriptase inhibitors. (1st November 2016) - Maiwald, Alexander; Hammami, Maya; Wagner, Sebastian; Heine, Andreas; Klebe, Gerhard; Steinmetzer, Torsten
Abstract: The type II transmembrane serine protease matriptase is a potential target for anticancer therapy and might be involved in cartilage degradation in osteoarthritis or inflammatory skin disorders. Starting from previously described nonspecific thrombin and factor Xa inhibitors we have prepared new noncovalent substrate-analogs with superior potency against matriptase. The most suitable compound35 (H-d -hTyr-Ala-4-amidinobenzylamide) binds to matriptase with an inhibition constant of 26 nM and has more than 10-fold reduced activity against thrombin and factor Xa. The crystal structure of inhibitor35 was determined in the surrogate protease trypsin, the obtained complex was used to model the binding mode of inhibitor35 in the active site of matriptase. The methylene insertion ind -hTyr andd -hPhe increases the flexibility of the P3 side chain compared to theird -Phe analogs, which enables an improved binding of these inhibitors in the well-defined S3/4 pocket of matriptase. Inhibitor35 can be used for further biochemical studies with matriptase.